Foliar or Bud Nematodes in Florida Strawberries - Johan Desaeger; Joseph W. Norling (EDIS, 2017)
Foliar or bud nematodes are liitle-known nematodes of the genus Aphelenchoides that were common in the early 1900's causing "crimp disease" of strawberries in Florida. Recently, these foliar nematodes have been observed again in the state, and seem to have come in with transplants from outside Florida. Foliar/bud nematodes can have a devastating effect on strawberries, as plants become stunted with curled up leaves, and little or no flowers and fruits are produced. No information is available on the biology and management of these nematodes in Florida. This publication aims to provide much needed information on these unknown pests. The following summarizes the different types of foliar nematodes, their biology, life cyclce, damage symptoms, survival strategies, dissemination, and management options.